Organising Freelancers: A Hard Case or a New Opportunity? - Wynn, Michael (Senate Hall, 2015)
Freelance workers present a special challenge in terms of collective labour organisation. As an individualistic and highly dispersed workforce, they are both difficult to recruit and represent. This paper explores the operational and legal difficulties that freelancers pose for trade unions in terms of collective representation. It is argued that freelancers have a range of distinctive needs and interests, that are accessible to trade union intermediation and that unions must adapt their traditional strategies if these needs are to be met. We conclude with an outline of particular methods and structures used by freelance unions in the UK and Europe. The paper indicates some of the constraints and opportunities for trade unions in organising the self-employed. Keywords: freelance, self-employed, unions, strategy, organisation
Keywords: freelance|self-employed|unions|strategy|organisation